Domains and determinants of retirement timing: A systematic review of longitudinal studies - Micky Scharn; Ranu Sewdas; Cécile R. L. Boot; Martijn Huisman; Maarten Lindeboom; Allard J. van der Beek (BMC, 2018)
Abstract Background To date, determinants of retirement timing have been studied separately within various disciplines, such as occupational health and economics. This narrative literature review explores the determinants of retirement timing in countries, and relevant domains among older workers from both an economic and occupational health perspective. Methods A literature search was conducted using 11 databases. Longitudinal studies on determinants of retirement timing were included. Study inclusion criteria were as follows: full-text article written in English or Dutch, conducted in humans, main outcome was time until retirement (i.e. retirement date or retirement age), and longitudinal design. Next, the included articles were screened for hypotheses on retirement timing and these articles with hypotheses were subjected to a quality assessment. Determinants for retirement timing were classified into multiple domains by three researchers. Results The literature search identified 20 articles. The determinants of retirement timing were classified into eight domains: demographic factors, health factors, social factors, social participation, work characteristics, financial factors, retirement preferences, and macro effects. In total, we identified 49 determinants, ranging from one (social, and retirement preferences) to 21 determinants (work characteristics) per domain. Conclusions The findings suggest that there is a wide range of determinants that influence retirement timing in modern industrialized countries and that these determinants differ between countries. We recommend that researchers include determinants from various domains when studying retirement timing, while taking into account a country's context.